Atherogenic properties of LDL particles after switching from Truvada or Kivexa plus lopinavir/r to lamivudine plus lopinavir/r: OLE-MET substudy. Issue 2 (4th March 2017) - Saumoy, Maria; Tiraboschi, Juan M.; Ordoñez-Llanos, Jordi; Ribera, Esteban; Domingo, Pere; Mallolas, Josep; Curto, Jordi; Gatell, Josep M.; Podzamczer, Daniel
Abstract : Background : The objective of this study was to determine the impact of tenofovir or abacavir discontinuation on low-density lipoprotein (LDL) phenotype and lipoprotein-associated phospholipase A2 (Lp-PLA2) activity in HIV-infected patients treated with lopinavir/ritonavir plus 2 nucleos(t)ide reverse transcriptase inhibitors (NRTI). Methods : Multicenter, open-label study. Patients were randomized to continue with lopinavir/ritonavir plus 2 NRTI (triple therapy) or to switch to lopinavir/ritonavir plus lamivudine (dual therapy). LDL phenotype (by gradient gel electrophoresis) and Lp-PLA2 (by 2-thio-PAF) were determined at baseline and week 48. Results : Forty-four patients included (triple therapy n = 19, dual therapy n = 25): men 63.6%, age 41.5 years (25–61), Framingham score 4.9% (0.2–22). Tenofovir was part of the regimen in 28 (63.6%) patients. Dual therapy patients were younger ( p = 0.013) and had lower baseline apolipoprotein A1 ( p = 0.029). At week 48, there were no changes in standard lipid measurements, except ApoA1/Apo B, which increased in dual therapy ( p = 0.038) with no differences between arms. At week 48, no change in LDL phenotype was found in either arm. No changes in total Lp-PLA2 activity or the relative distribution of LDL and HDL particles were found at week 48 in either arm. Conclusions : Discontinuing the third nucleos(t)ide, mainly tenofovir and abacavir, in a lopinavir/ritonavir-containing regimen was not associated with a deleterious effect on LDL phenotype nor in Lp-PLA2 activity.